Nasionalisme dan Perjalanan Demokrasi - Asnawi Umar Ali (Universitas Islam Indonesia, 2005)
In Indonesia the nationalism discourse has been placed on the debate between Tjipto Mangoen Koesoemo and Soetatmo Soerjokoesoemo. Tjipto established the Budi Utomo and the Indische Partij, meanwhile Soetomo founded the Javanese Nationalism Comiittee. In 1918 the debate was published as flyers entitle